EXPERIMENTAL STUDY ON THE DEVELOPMENT OF THE OPTIMUM EXPOSURE CONDITIONS OF LOW-FREQUENCY ULTRASOUND ON SOFT TISSUE OF THE LOWER JAW - Hasimova, Z.V.; Гасанов І. А.; Гашимов Р. Г. (World of Medicine and Biology, 2015)
For the development purpose of a method of efficiency increase of orthodontic treatment for tients with maloclusions caused by a teeth impaction, and reductions of treatment terms, the pilot study by definition of the optimum modes of single influence by low-frequency ultrasound on gum tissue of the mandible of white rats within 1-10 seconds is conducted. As a result of research expediency of application in clinical practice of low-frequency ultrasound is determined by the device "SIAZ-EGS" in the mode of 5-10 seconds for stimulation of an impacted teeth eruption.
Keywords: low frequency ultrasound (NHI); impacted teeth; experimental exposure; the gingival tissue